Users satisfaction towards the UiTM Pahang workshop layout / Hanani Yuhaniz and Norhafizah Rosman - Yuhaniz, Hanani; Rosman, Norhafizah (2011)
The workshop in UiTM Pahang gives opportunity to students to practice and have hands-on learning experience with machines. This study is intended to provide insights about the satisfactions of users towards the UiTM Pahang workshop layout. The case study involves 3 different groups of users which are the students, staffs and users outside the University. By having a well developed layout, it is then the users can make use of-the floor efficiently and effectively. Based on the results of the survey, most users were satisfied with the current workshop layout. However, many agree on the workshop need improvements in order to be ready for future usage, especially in achieving the aspiration of UiTM being a world class University.